Deletion of Synechocystis sp. PCC 6803 leader peptidase LepB1 affects photosynthetic complexes and respiration - Zhang, Lifang (2021)
The cyanobacterium Synechocystis sp. PCC 6803 possesses two leader peptidases, LepB1 (Sll0716) and LepB2 (Slr1377), responsible for the processing of signal peptide-containing proteins. Deletion of the gene for LepB1 results in an inability to grow photoautotrophically and an extreme light sensitivity. Here we show, using a combination of Blue Native/SDS-PAGE, Western blotting and iTRAQ analysis, that lack of LepB1 strongly affects the cell's ability to accumulate wild-type levels of both photosystem I (PSI) and cytochrome (Cyt) b6f complexes. The impaired assembly of PSI and Cyt b6f is considered to be caused by the no or slow processing of the integral subunits PsaF and Cyt f respectively. In particular, PsaF, one of the PSI subunits, was found incorporated into PSI in its unprocessed form, which could influence the assembly and/or stability of PSI. In contrast to these results, we found the amount of assembled photosystem II (PSII) unchanged, despite a slower processing of PsbO. Thus, imbalance in the ratios of PSI and Cyt b6f to photosystem II leads to an imbalanced photosynthetic electron flow up- and down-stream of the plastoquinone pool, resulting in the observed light sensitivity of the mutant. We conclude that LepB1 is the natural leader peptidase for PsaF, PsbO, and Cyt f. The maturation of PsbO and Cyt f can be partially performed by LepB2, whereas PsaF processing is completely dependent on LepB1. iTRAQ analysis also revealed a number of indirect effects accompanying the mutation, primarily a strong induction of the CydAB oxidase as well as a significant decrease in phycobiliproteins and chlorophyll/heme biosynthesis enzymes.